Intermittent screening and treatment with artemether–lumefantrine versus intermittent preventive treatment with sulfadoxine–pyrimethamine for malaria in pregnancy: a facility-based, open-label, non-inferiority trial in Nigeria - Ekpereonne Esu; Nicole Berens-Riha; Michael Pritsch; Nuria Nwachuku; Thomas Loescher; Martin Meremikwu (Malaria Journal, 2018)
Abstract Background The spread of SP resistance may compromise the effectiveness of intermittent preventive treatment of malaria in pregnancy (MiP) with sulfadoxine–pyrimethamine (IPTp-SP) across Africa. However, there is no recommended alternative medicine for IPTp or alternative strategy for prevention of MiP. This poses problems for the prevention of MiP. This study investigated, whether screening with a rapid diagnostic test for malaria at routine antenatal clinic attendances and treatment of only those who are positive (intermittent screening and treatment) with artemether–lumefantrine is as effective and safe as IPTp-SP in pregnant women. Methods During antenatal clinic sessions at the General Hospital Calabar, Nigeria, held between October 2013 and November 2014, 459 pregnant women were randomized into either the current standard IPTp-SP or intermittent screening and treatment with artemether–lumefantrine (ISTp-AL). All women received a long-lasting insecticide-treated net at enrolment. Study women had a maximum of four scheduled visits following enrolment. Haemoglobin concentration and peripheral parasitaemia were assessed in the third trimester (36–40 weeks of gestation). Birth weight was documented at delivery or within a week for babies delivered at home. Results In the third trimester, the overall prevalence of severe anaemia (Hb < 8 g/dl) and moderate (8–10.9 g/dl) anaemia was 0.8 and 27.7%, respectively, and was similar in both treatment groups (p = 0.204). The risk of third-trimester severe anaemia did not differ significantly between both treatment arms (risk difference − 1.75% [95% CI − 4.16 to 0.66]) although the sample was underpowered for this outcome due to several participants being unavailable to give a blood sample. The risk of third-trimester maternal parasitaemia was significantly lower in the ISTp-AL arm (RD − 3.96% [95% CI − 7.76 to − 0.16]). The risk of low birthweight was significantly lower in the ISTp-AL arm after controlling for maternal age, gravidity and baseline ...